Sources of Reading Anxiety among the Learners of Turkish as a Foreign Language - ALTUNKAYA, Hatice; ATEŞ, Ayşe (Asian Journal of Education and Training, 2018)
Language instruction is conducted by utilizing the data provided by contemporary educational sciences and based on the fact that learning is both a cognitive and affective process. Instruction of reading skills, one of the four basic language skills in Turkish as a foreign language instruction, is a complex process that range from the introduction of sounds to the reading comprehension process. During this education, in addition to cognitive training of learners, reading anxiety, which is considered as an affective dimension of reading, can also be considered as a factor that affect the reading process. The present study was conducted with the interview technique, which is one of the qualitative research methods. A focus group interview was conducted with six Turkish instructors as a foreign language and eight students learning Turkish as a foreign language using the developed semi-structured interview form. In the study, the sources of reading anxiety in learning Turkish as a foreign language were determined as "tonal attributes and pronunciation", "language levels (Course levels A1, A2, B1, B2, C1, C2)", "the fact that Turkish is an agglutinative language", "properties of reading texts", "unknown words" “unknown topics", "culture" and "fear of making mistakes".